2001
DOI: 10.1152/ajpheart.2001.281.3.h1372
|View full text |Cite
|
Sign up to set email alerts
|

Existence of cardiac PNMT mRNA in adult rats: elevation by stress in a glucocorticoid-dependent manner

Abstract: Phenylethanolamine N-methyltransferase (PNMT) is the enzyme that synthesizes epinephrine from norepinephrine. The aim of this study was to determine potential PNMT gene expression in the cardiac atria and ventricles of adult rats and to examine whether the gene expression of this enzyme is affected by immobilization stress. PNMT mRNA levels were detected in all four parts of the heart, with the highest level in the left atrium. Both Southern blot and sequencing verified the specificity of PNMT detected by RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 41 publications
10
57
1
Order By: Relevance
“…In this work, we observed that CSITR induces the decrease of CORT concentration in the plasma, coinciding with the decrease of PNMT mRNA level in the adrenal medulla. Studies on the hypophysectomised rats have shown that reduced amounts of corticosteroids cause the reduction of level of PNMT mRNA level (Evinger et al 1992, Wong et al 1995, Krizanova et al 2001. A significant result in this study is that CSITR induces the increase of PNMT protein level in the adrenal medulla, with the consequent increase of A level in the plasma.…”
Section: Imm and Csitr+imm Treatmentssupporting
confidence: 51%
“…In this work, we observed that CSITR induces the decrease of CORT concentration in the plasma, coinciding with the decrease of PNMT mRNA level in the adrenal medulla. Studies on the hypophysectomised rats have shown that reduced amounts of corticosteroids cause the reduction of level of PNMT mRNA level (Evinger et al 1992, Wong et al 1995, Krizanova et al 2001. A significant result in this study is that CSITR induces the increase of PNMT protein level in the adrenal medulla, with the consequent increase of A level in the plasma.…”
Section: Imm and Csitr+imm Treatmentssupporting
confidence: 51%
“…Second, the adrenal medulla releases not only EPI but also NE, chromogranin A, catestatin, pancreastatin, neuropeptide Y, and other hormones. Third, EPI synthesis is concentrated in the adrenal medulla but also is present in many adult tissues outside the adrenal such as heart [15][16][17] and blood vessels. 18 These peripheral tissues might make enough EPI to tonically stimulate adrenergic receptors locally because EPI is a potent agonist of adrenergic receptors, especially the ␤ 2 -adrenergic receptor, for which it has a much higher affinity than any other known endogenous compound.…”
Section: Clinical Perspective P 1031mentioning
confidence: 99%
“…These results are in good agreement with previous observations . Increased adrenaline levels in ventricles are consequence of stress-induced uptake from circulation or of increased endogenous adrenaline synthesis directly in the heart (Axelrod 1962; Krizanova et al 2001). These data show specific elevation of catecholamines in the heart chamber and allow correlating these changes with changed protein and gene expression, as shown in Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The pellet was dissolved in homogenization solution, and protein concentration was determined according to Bradford (1976). Western blot analysis was carried out as described previously (Krizanova et al 2001). Briefly, protein extract from the cardiac ventricles (50-180 mg) was separated by SDS-PAGE and then transferred to a supported nitrocellulose membrane (Hybond-ECL, AP Biotech) using semidry blotting.…”
Section: Protein Isolation and Relative Quantification Of Protein Levmentioning
confidence: 99%